Therapeutic Exercise in Systemic Lupus Erythematosus: Review Article - Rahmatika R; Rudy Handoyo; Tanti Ajoe K (Indonesian Journal of Physical Medicine & Rehabilitation, 2018)
Introduction: Systemic Lupus Erythematosus (SLE) is a prototype of an autoimmune disease characterized by the production of antibodies against cell nucleus components with a broad spectrum of clinical patterns. The SLE will cause long-term complications so that SLE patients tend to have sedentarylifestyle and decrease physical activity which reduces exercise capacity. The aim of therapeutic exercise is to improve a variety of clinical symptoms in SLE patients by alleviate the inflammatory process and modifying the disease’s natural course.Methods: All of references have searched in 2018 within the areas of rheumatology, immunology, cardiology, physical education and physiotherapy.Results: Therapeutic exercise in SLE has an anti-inflammatory effect by inhibiting the release of inflammatory mediators including TNF-α. Therapeutic exercise in the form of aerobic and resistance exercise able to improve aerobic capacity, reduced fatigue, increasing chronotropic reserve, heart raterecovery, functional performance, functional capacity, muscle strength and increase bone turn over. Therapeutic exercise was not aggravated disease activity as measured by SLE Activity Index (SLEDAI) and SLE Activity Measure (SLAM) index.Conclusion: Supervised aerobic and resistance exercise seems to help improve health, vitality and self perceived physical capacity in SLE patients.Keywords: Systemic lupus erythematosus , therapeutic exercise, SLEDAI, SLAM index